Images /. - Aas, Oliver (Diacritics, 2023)
Yevgen Samborsky is a multihyphenate, whose work spans not only painting but also video work, installation, and community-based creative projects. His visual language is entirely intermedial: he draws on photography, graffiti, hyperrealism, and internet machine aesthetics. His indebtedness to the digital image has been particularly strong in the last two years, which he has spent watching the news from back home on his com-puter. He has taken pictures of destroyed cultural institutions like the Kharkiv Art Museum or the Odessa Museum and incorporated them into his more abstract painterly meditations on war and displacement. As part of his process of digital reworking, he combines his memo-ries of a place, the current events in Ukraine, and his own affective charge.